Diet of Elagatis bipinnulata (Guoy & Gaimard, 1824) in Côte d’Ivoire (Gulf of Guinea) - Florentine, Assan N’dri; Constance, Diaha N’guessan; Justin, Amande Monin; Paul, Angui Kouamé Jean; Yao, N’guessan; Abekan, Edoukou; Konan, N’da; Marie, Guillou Aurélie (European Scientific Journal, ESJ, 2019)
The rainbow runner, Elagatis bipinnulata, which belongs to the Carangidae family, is regularly encountered in the landing of artisanal fishing in Abobo-Doumé (Republic of Côte d’Ivoire). The object of this work is to study the diet of Elagatis bipinnulata according to the marine seasons and the size of the various specimens (immature and mature). About 900 fish measuring between 43 and 93 cm (fork length - FL) were examined from September 2015 to August 2017. On the 900 examined stomachs, 541 were empty, which is giving a vacuity coefficient of 60.11%. A feeding index (IRI: index of relative importance of food item) combining three methods percentage occurrence, numerical method and weight method) was used. The identification of the items found in the stomach contents revealed that the principals food items were fish (%IRI=48.85) and crustaceans (%IRI=45.78). Cephalopods (%IRI=4.17), fish detritus (%IRI=1.2) and crustaceans (Portunus puber) (%IRI=0.55) are accidental food. The diet of the species does not change according to the seasons and the size of fish.